Legal Politics: Personal Data Protection in Peduli Protect Applications in Indonesia - Irmanjaya Thaher (Publikasi Indonesia, 2022)
The purpose of this study was to determine the application of personal data protection to the use of the Peduli Protect. This is because, application users are required to register an account which will automatically include personal data. Practically, the use of the Peduli Protect application can benefit the wider community even though it has to intersect with the protection of personal data. The author finds that the implementation of the Cares Protect application is still vulnerable to misuse of personal data, therefore comprehensive and detailed rules are needed to protect users of the Care Protect application. So, the use of the Care Protect application to stop the spread of Coronavirus Disease (COVID-19) which relies on public awareness and participation can run effectively without any misuse of personal data and clear sanctions for violators after the COVID-19 pandemic ends.